Synthesis of high belite sulfoaluminate cement with high volume of mixed solid wastes. (August 2022) - Wang, Xiaoli; Guo, Ming-Zhi; Yue, Gongbing; Li, Qiuyi; Ling, Tung-Chai
Abstract: Synthesis of high belite sulfoaluminate cement at low sintering temperatures (1225–1300 °C) using petroleum coke desulfurization residue (PCDR), fly ash (FA), carbide slag (CS), and bauxite (BX) was investigated. The thermal behavior, mechanical properties, heat of hydration, and hydration products of the developed binder were systematically studied. The results showed that the target C4 A3 S, β-C2 S, and C4 AF phases were successfully produced at 1225–1300 °C, and the industrial solid wastes can use up to 80%. The optimal sintering condition to obtain satisfactory clinker strength was 1300 °C, 45 min, and 10 °C/min, and the corresponding 1-d and 28-d strengths were 27.7 and 51.4 MPa. The early hydration products were mainly composed of AFt, AH3, unhydrated C4 A3 S, C2 S, CaSO4, and trace CH. The network structure formed by AFt interweaving was filled with AH3 colloid, which was conducive to the improvement of cement strength. Furthermore, the cumulative heat release of the developed cement (191 J/g) in 3-d was lower than that of the sulphoaluminate cement (SAC) (198 J/g), effectively alleviating the rapid setting as compared to SAC and broadening its application range.